Analisis Authentic Personal Branding Fashion Blogger Olivia Lazuardy (Studi Deskriptif terhadap Akun @olivialazuardy) - Emika Vallerie Huzafahmazidah; Dini Salmiyah Fithrah Ali (UNIVED PRESS, Universitas Dehasen Bengkulu, 2017)
Instagram is a social media that often used nowadays. Instagram can be the media for a person to build a Personal Branding in order to reach certain visions. Fashion Blogger can use Instagram to communicate visually through picture uploads on their profile. In order to compete in the market and to be authentic, Fashion Blogger need an Authentic Personal Branding. Olivia Lazuardy is a Fashion Blogger that has been receiving awards in the fashion industry for the past 2 years. The purpose of this study is to learn the application of Authentic Personal Branding Criterias that Olivia Lazuardy applied as a Fashion Blogger. The result of the study is that Olivia is authentic, has consistency, is relevant to her audience interests, has a visibility, can be called as an effective leader, have a good relationship with followers and brands, and has a good performance. Researcher suggests that Olivia should pay more attention to make a differentiation to be the most superior in the market as a Fashion Blogger. Moreover, researcher also suggests that Olivia should build a wider network by managing relationship with local brands.